A psychology in our own language: Redefining psychology in an African context - Segalo, Puleng; Cakata, Zethu (PINS-Psychology in Society, 2017)
Psychology in Africa has for a long time and continues to be a contentious subject. Many scholars have pointed to the importance of acknowledging multiple forms of knowing and being in the world and understanding the complexities of understanding how people make meaning of their world. The urge to understand and define the notion of being human in universalistic terms minimises and obscures the complexities of human experiences in time, space and geolocation. This paper argues for the need to take the role of languages (indigenous) earnestly if we are to imagine a psychology (African) that takes local contexts within which it is practised and taught seriously. Furthermore, we insist on the importance of decolonising the psychology curriculum wherein what is deemed as legitimate at the exclusion of other forms of knowing becomes challenged.